PENGARUH MELIHAT KONTEN FOOD VLOGGER INSTAGRAM @KOKODIETT TERHADAP KEPUTUSAN PEMBELIAN FOLLOWERS - Safira, Alifa Salma; ., Mutiah (The Commercium, 2025)
This study aims to analyze the influence of viewing Instagram content from food vlogger @kokodiett on the purchasing decisions of followers. Using the AIDDA (Attention, Interest, Desire, Decision, Action) theory as an analytical framework, this research explores how the visual and narrative content presented by the food vlogger can affect followers' purchase intentions and actions. Data were collected through an online survey involving 100 respondents. This is a quantitative study utilizing both primary and secondary data collected through observation, questionnaires, and documentation. The results of the regression analysis indicate that the food vlogger's content has a significant influence on purchasing decisions, with a regression coefficient of 38.6%, suggesting that while this content influences purchasing decisions, other factors also play a role. This study is expected to be used to enhance marketing content factors to better satisfy customers and encourage purchases, as well as to serve as a reference for further research. Keyword: Instagram Content, Food Vlogger, Purchase Decision